The most balance composition of calcium-phosphorus in the feed to support growth performance and tibia profile of broiler chicken strain CP 707 - Charles Venirius Lisnahan; Afred Nubatonis (Livestock and Animal Research, 2021)
Objective: Calcium and phosphorus are macrominerals that are needed for metabolism and mineralization of chicken bones. This study aims to determine the growth performance and tibial profile of broiler chicken strain CP 707 which are fed by using different calcium-phosphorus balance compositions.Methods: This research was conducted in Kefamenanu, the East Nusa Tenggara for 42 days. A total of 96 day old chicks were used in this study. Chickens were allocated in 16 units of cages, based on a completely randomized design consisting of 4 treatments and 4 replications. The treatments given were T0 (control feed without calcium-phosphorus supplementation), T1 (control feed + 1.0% calcium + 0.5% phosphorus), T2 (control feed + 1.5% calcium + 0.5% phosphorus) and T3 (control feed + 2.0% calcium + 0.5% phosphorus).Results: The findings showed that the calcium-phosphorus ratio affected weight gain, feed conversion, carcass weight, tibial bone weight, tibial bone dry weight and tibial bone ash content (P<0.05), while feed consumption and tibial bone length were not significant. The highest body weight was in T3 (2142.25±31.84 g/bird) with a weight gain of 62.41±2.20 g/bird/day. The best feed conversions at T2 and T3 were 1.94±0.33 and 1.85±0.70. The highest carcass weight at T3 was 1354.45±39.12 g/bird with a carcass percentage of 63.20±0.32%. The highest tibial weight at T2 and T3 were 18.57±0.73 and 19.43±0.66 g/bird with dry weight of 40.61±0.75 and 41.42±1.33%. The highest tibial bone ash content was at T3, namely 44.72±0.91%.Conclusions: The conclusion of this study is that the balance of 2.0% calcium and 0.5% phosphorus provides optimal growth performance and tibial profile.